Analisis Model Pembelajaran Pendidikan Pancasila Kelas III Sekolah Dasar Negeri Kadipiro - Ariedasita Calleza Aulia; Rahma Khoirun Nisa; Sharofina Putri Endiana; Endrise Septina Rawanoko (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the improvement of students’ knowledge and the alignment of the Civic Education learning model with the characteristics of third-grade students at SDN Kadipiro. The research problem arises from the tendency of Civic Education in elementary schools to rely heavily on lecture-based instruction, which results in low student engagement and limited comprehension of abstract concepts such as rights and obligations. A descriptive qualitative approach was employed through observations, interviews, and documentation to obtain a comprehensive picture of the learning process, the instructional model applied, and classroom dynamics. The findings reveal that the teacher implemented a game-based Discovery Learning model that emphasizes exploration, categorization, verification, and independent conclusion-making by students. This model proved effective, as evidenced by 85% of students being able to understand and distinguish examples of rights and obligations in accordance with the Civic Education learning outcomes. The study also indicates that game-based learning is more compatible with the students’ predominant visual and kinesthetic learning tendencies, enabling them to maintain focus more effectively than when using traditional lecture methods. However, several challenges emerged, including variations in students’ writing literacy skills and the absence of a structured assessment rubric. These findings underscore the need for flexible instructional design, the integration of concrete learning media, and the implementation of more systematic formative assessment practices. Future research is recommended to develop differentiated instructional strategies and to utilize more diverse media to accommodate the needs of heterogeneous classrooms.